The Use of Sevima Edlink as an Online Learning Media in Indonesian Language Subjects - Arumdani, Arsy; Nawir, Muhammad; Nasir (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe: 1) the use of the Sevima Edlink platform as an online learning medium in Indonesian language subjects in grade VII; 2) the effectiveness of the Sevima Edlink platform as an online learning medium in Indonesian language subjects in grade VII. The study took place in the odd semester of the 2024/2025 academic year at SMP Negeri 33 Makassar. This study employed a qualitative approach, utilizing a case study method. The study's informants consisted of three Indonesian language teachers and six grade VII students. Data collection techniques were carried out through observation, interviews, and documentation. Observations were conducted using established observation guidelines. Interview guidelines were used for interview activities. All instruments were arranged objectively and systematically. Data were analyzed using a thematic approach. The results showed that the use of Sevima Edlink helped the learning process become more structured and flexible. Teachers felt helped in distributing materials and assignments systematically, while students found it easier to access and understand learning independently. Although several obstacles were encountered, such as internet connectivity issues and adapting to the use of applications, this did not hinder the teaching and learning process. Thus, Sevima Edlink is considered worthy and adequate for use as an online learning medium, especially in supporting the digitalization of education in the modern era.